Invisible girl : a novel - Jewell, Lisa (Atria Books, 2020)
"The author of the "rich, dark, and intricately twisted" (Ruth Ware, New York Times bestselling author) The Family Upstairs returns with another taut and white-knuckled thriller following a group of people whose lives shockingly intersect when a young woman disappears. Owen Pick's life is falling apart. In his thirties, a virgin, and living in his aunt's spare bedroom, he has just been suspended from his job as a geography teacher after accusations of sexual misconduct, which he strongly denies. Searching for professional advice online, he is inadvertently sucked into the dark world of incel-involuntary celibate-forums, where he meets the charismatic, mysterious, and sinister Bryn. Across the street from Owen lives the Fours family, headed by mom Cate, a physiotherapist, and dad Roan, a child psychologist. But the Fours family have a bad feeling about their neighbor Owen. He's a bit creepy and their teenaged daughter swears he followed her home from the train station one night. Meanwhile, young Saffyre Maddox spent three years as a patient of Roan Fours. Feeling abandoned when their therapy ends, she searches for other ways to maintain her connection with him, following him in the shadows and learning more than she wanted to know about Roan and his family. Then, on Valentine's night, Saffyre Maddox disappears-and the last person to see her alive is Owen Pick. With evocative, vivid, and unputdownable prose and plenty of disturbing twists and turns, Jewell's latest thriller is another "haunting, atmospheric, stay-up-way-too-late read" (Megan Miranda, New York Times bestselling author)"--